Discovering potential sources of emerging pathogens: South America is a reservoir of generalist avian blood parasites. Issue 1 (January 2016) - Moens, Michaël A.J.; Pérez-Tris, Javier
Graphical abstract: Highlights: Ecuadorian avifauna hosts generalist Haemoproteus parasites. Parasites have independently evolved into generalists in megadiverse area. South America is a reservoir of generalist Haemoproteus parasites. Abstract: Generalist pathogens are capable of infecting a wide range of host species, and may pose serious disease emergence threats if accidentally moved outside their native areas. To date little effort has been devoted to identifying geographic areas that may act as reservoirs of generalist pathogens. According to current theory, where host diversity is high, parasite specialisation in one host species may be penalised by reduced host availability, while generalist parasites may benefit from the exploitation of various host species. Therefore natural selection could favor generalist parasites where host diversity is high. Here we explored if, in a highly diverse bird community in Ecuador, a generalist strategy is promoted among local Haemoproteus and Plasmodium blood-borne parasites compared with similar parasite communities throughout the world. We reconstructed the phylogenetic relationships of every parasite lineage in order to understand the evolution of host specificity in this megadiverse area. We found high levels of host generalisation for both parasite genera, and the mean host range of the Haemoproteus community in Ecuador was significantly higher than other parasite communities in other areas outside the Neotropics. Generalist Haemoproteus parasites in this bird community had diverse phylogenetic ancestry, were closely related to specialist parasites and were apparently endemic to the Amazon, showing that different parasites have independently evolved into host generalists in this region. Finally we show that Haemoproteus communities in Ecuador and South America are more generalist than in temperate areas, making this continent a hotspot of generalist Haemoproteus parasites for wild birds.